2020
DOI: 10.1098/rspb.2020.2531
|View full text |Cite
|
Sign up to set email alerts
|

Vocal convergence in a multi-level primate society: insights into the evolution of vocal learning

Abstract: The extent to which nonhuman primate vocalizations are amenable to modification through experience is relevant for understanding the substrate from which human speech evolved. We examined the vocal behaviour of Guinea baboons, Papio papio , ranging in the Niokolo Koba National Park in Senegal. Guinea baboons live in a multi-level society, with units nested within parties nested within gangs. We investigated whether the acoustic structure of grunts of 27 male baboons of two gangs varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Although recent work calls for careful adjustments in categorizing vocal learning abilities along a multidimensional space [ 12 ], we applied a conservative approach in our choice to characterize species as vocal learners. We excluded, for instance, cases of vocal convergence, seen in Guinea baboons [ 11 ] and chimpanzees [ 21 ], although these could be considered part of a broad vocal learning contiguum [ 12 ]. We, therefore, classified as vocal learners the species that belong to the four non-human mammalian clades for which vocal learning has been shown in the form of VPL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although recent work calls for careful adjustments in categorizing vocal learning abilities along a multidimensional space [ 12 ], we applied a conservative approach in our choice to characterize species as vocal learners. We excluded, for instance, cases of vocal convergence, seen in Guinea baboons [ 11 ] and chimpanzees [ 21 ], although these could be considered part of a broad vocal learning contiguum [ 12 ]. We, therefore, classified as vocal learners the species that belong to the four non-human mammalian clades for which vocal learning has been shown in the form of VPL.…”
Section: Methodsmentioning
confidence: 99%
“…Second, selective pressures may also have favoured the emergence of vocal learning abilities without necessarily affecting acoustic allometry relationships. For instance, Fischer et al [11] recently demonstrated that vocal convergence in Guinea baboons was dependent on the amount of social interactions between individuals, therefore showing that some implicit forms of vocal learning can likely originate from social factors, and that allometry scaling need not be affected for a species to exhibit vocal learning abilities. In addition to confirming other vocal convergence results in this clade [21], Fischer et al's study also reaffirms the need to consider vocal learning as a multidimensional space transcending the limitation of vocal learning to 'vocal production learning', even when the latter is thought of as a continuum [11,12].…”
Section: (C) Magnitude and Direction Of Residuals: The Regression Line As Watershed Between Vocal Production Learning And Non-vocal Produmentioning
confidence: 99%
“…The main body of recent evidence for vocal flexibility in nonhuman primates comes from studies on vocal convergence within call types ( figure 1 ). Several studies reported greater acoustic similarities between closely associated animals that were not genetically related than between non-associates, including grey mouse lemurs ( Microcebus murinus ) [ 73 ], Campbell's monkeys ( Cercopithecus campbelli ) [ 74 ], Guinea baboons ( Papio papio ) [ 75 ] ( figure 2 c ) and chimpanzees ( Pan troglodytes ) [ 76 ]. To further investigate the process of convergence, studies have documented call characteristics before and after housing animals with previously unknown conspecifics.…”
Section: Primatesmentioning
confidence: 99%
“…Guinea baboons (Papio papio) [75] (figure 2c) and chimpanzees (Pan troglodytes) [76]. To further investigate the process of convergence, studies have documented call characteristics before and after housing animals with previously unknown conspecifics.…”
Section: But Learningmentioning
confidence: 99%
“…Animal sounds can also be used as indicators of social relationships. For example, for some primate species, certain call types are known to correlate with social ranks within the group [12][13][14]. In terms of animal welfare, vocalizations can also be used as indicators.…”
Section: Introductionmentioning
confidence: 99%